Studi Longitudinal: Stabilitas dan Perubahan Minat Karier Pada Siswa Laki-Laki dan Perempuan - Mudhar, Mudhar; Aisyah, Aisyah; Mufidah, Elia Firda; Nastiti, Dwi (Universitas Nusantara PGRI Kediri, 2022)
Changes in career interests last until they find a career field that is considered according to their potential and competence. Early adolescence is a time of searching, so their career interests are still changing. This study was conducted to determine changes in career interest in male and female students. The longitudinal study was conducted with two measurements, namely at the beginning of junior high school (grade VII) and at the end of school in junior high school (grade IX). The participants were 169 students consisting of 108 girls and 61 boys. The instrument used is RMIB (Rothwell Miller Interest Blank). Data analysis uses quantitative descriptive analysis to see changes in career interests that occur in each student. The results showed that there were 67.55% of students whose career interests changed or were not stable. More male students have stable career interests than female students. For male students, there are 49.18% of students whose interests are stable, while for female students, there are only 23.15% of students who are stable.